2017
DOI: 10.1021/acsnano.7b06131
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Lanthanum Tantalate Perovskite Nanosheets Modified by Nitrogen Doping for Efficient Photocatalytic Water Splitting

Abstract: Ultrathin nitrogen-doped perovskite nanosheets LaTaON have been fabricated by exfoliating Dion-Jacobson-type layered perovskite RbLaTaON. These nanosheets demonstrate superior photocatalytic activities for water splitting into hydrogen and oxygen and remain active with photon wavelengths as far as 600 nm. Their apparent quantum efficiency under visible-light illumination (λ ≥ 420 nm) approaches 1.29% and 3.27% for photocatalytic hydrogen and oxygen production, being almost 4-fold and 8-fold higher than bulk Rb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…H 2 , as a renewable energy with high energy density and no secondary pollution, can effectively alleviate the current energy crisis and environmental pollution. In consideration of the advantages of ultrathin 2D semiconductors, various efforts have been devoted to construct high‐efficiency photocatalytic H 2 production photocatalysts and the study results undoubtedly demonstrated that the ultrathin 2D materials show excellent photocatalytic H 2 production activity . However, most semiconductors exhibit low yield of the H 2 due to the high recombination rate of photogenerated electrons and holes.…”
Section: Energy and Environment Applicationsmentioning
confidence: 99%
“…H 2 , as a renewable energy with high energy density and no secondary pollution, can effectively alleviate the current energy crisis and environmental pollution. In consideration of the advantages of ultrathin 2D semiconductors, various efforts have been devoted to construct high‐efficiency photocatalytic H 2 production photocatalysts and the study results undoubtedly demonstrated that the ultrathin 2D materials show excellent photocatalytic H 2 production activity . However, most semiconductors exhibit low yield of the H 2 due to the high recombination rate of photogenerated electrons and holes.…”
Section: Energy and Environment Applicationsmentioning
confidence: 99%
“…However, it cannot be denied that the rapid recombination rate of photo-induced carries is a main inhibiting factor for those materials displaying excellent catalytic performance adequately [24][25][26][27][28] . Fortunately, MOFs materials are good platforms with large surface area and a lot of functional groups to hybridize with other materials to form heterostructures to improve the photocatalytic ability [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Narrow band gap semiconductors, on the other hand, have stability issues during water splitting reactions such as SiC and InP . In this regard, a wealth of metal nitrides and oxynitrides have gained considerable interest not only because they own small band gap values (~2 eV) but also because they have proper band edge positions that meet thermodynamic requirements for water splitting reactions . In particular, perovskite oxynitrides such as AM(O, N) 3 (A = La, Y, Ca, Sr, Ba; M = Ti, Nb, Ta) have shown to be visible light active photocatalysts for water splitting reactions .…”
Section: Introductionmentioning
confidence: 99%
“…12,14 In this regard, a wealth of metal nitrides and oxynitrides have gained considerable interest not only because they own small band gap values (~2 eV) but also because they have proper band edge positions that meet thermodynamic requirements for water splitting reactions. 15,16 In particular, perovskite oxynitrides such as AM(O, N) 3 (A = La, Y, Ca, Sr, Ba; M = Ti, Nb, Ta) have shown to be visible light active photocatalysts for water splitting reactions. 17,18 Nevertheless, previous investigations suggest that these compounds generally exhibit poor photocatalytic activities under ordinary conditions, being incommensurate to their strong visible light absorption.…”
Section: Introductionmentioning
confidence: 99%